Pengembangan Media Pembelajaran Kirandalam (Kincir Kerajaan Hindu, Budha dan Islam) Untuk Meningkatkan Hasil Belajar Pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Diyah Lisnawati; Firosalia Kristin (Universitas Muhammadiyah Gresik, 2024)
Students have difficulty understanding the history of the Hindu, Buddhist, and Islamic kingdoms in science learning because teachers do not use additional media during learning. This study aims to develop media and to determine the level of validity of the